PENGARUH PERSEPSI KEGUNAAN, E-SERVICE QUALITY, DAN E-LOYALTY PROGRAM TERHADAP MINAT MENGGUNAKAN ULANG WEBSITE GRAMEDIA ONLINE - WELLIAM, TRIBOWO (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Perceived usefulness is a level which a person believes that users of a particular system will to improve the person's work. The perception of e-service quality is assessment of the consumer regarding the extent to which a website to facilitate the efficient and effective expenditures in terms of purchase, and shipping. E-loyalty program is the process of making the consumer has feel liked, enriched, smart by their companies and it takes to build relationships and the intensity of the relationship between consumers with online retailers. This research aims to research more about the influence of perceived usefulness, e-service quality, and e-loyalty programs of interest to use the website Gramedia online. In this research is used in the study of conclusive causal research. The techniques to take sampling used isnon-probability sampling. This type of method used is the purposive sampling. The sample used was 150 consumer websites Gramedia online. The Data were collectedby questionnaire. The data were analysed using multiple linear regression analysis. The analysis’ result shew that the perceived usefulness, e-service quality, and e-loyalty program had significant in using the website Gramedia online. In this study, it was found that the perceived usefulness cannot be a moderator for the relationship between e-service quality, and e-loyalty towards interest using the website Gramedia online.